The Customer Perceived Orientation Effect on Perceived Value and Customer Satisfaction and Its Influence on Customer Trust - Halimatussakdiah, Halimatussakdiah; Suryani, Irma; Zuhra, Syarifah Evi (Universitas Muhammadiyah Yogyakarta, 2023)
Research aims: The purpose of this research is to examine the impact of customer-perceived orientation (CPO) on customer-perceived value (CPV) and customer satisfaction (CS) and its influence on customer trust (CT) in Islamic banks.Design/Methodology/Approach: The study employed a quantitative research design with a descriptive survey. Data from 270 Islamic bank customers were analyzed using Structural Equation Modeling Analysis of Moment Structure (SEM-AMOS).Research findings: Based on the findings, CPO significantly affected CPV and CS. Furthermore, CS and CPV also had a significant impact on CT.Theoretical contribution/originality: The study strengthens the body of knowledge on customer perceived orientation, perceived value, satisfaction, and trust.Practitioner/Policy implication: The research highlights the significance of the investigated variables and guides policymakers and scholars.Research limitation/Implication: Several limitations could be identified. Firstly, primary data were collected cross-sectionally so that future studies can apply longitudinal research to understand investigated variables better. Secondly, the small sample size of 270 consumers may not be recommended to generalize a vast population. For future research, it is suggested that the proposed model be validated with a larger sample size.